Ligand Based Pharmacophore Modelling, Virtual Screening, Molecular Docking, and ADMETOX of Natural Compounds as Antibiotic Candidates against Urinary Tract Infections (UTI) - Windy Dwininda; Linda Erlina; Rafika Indah Paramita; Fadillah Fadillah; Surya Dwira; Jaka Fajar Fatriansyah (EKSAKTA: Berkala Ilmiah Bidang MIPA, 2023)
The use of antibiotic drugs requires close supervision that patients take antibiotics according to the rules. Irregular antibiotic use led to increased ADR cases (Antibiotic Drug-resistant). ADR is when an individual becomes resistant to an antibiotic drug that cannot kill bacteria. The high number of ADR cases prompted drug discovery to be implemented in analysis for Antibiotic candidates with good effectiveness through the Molecular Docking approach. The search for candidate test compounds as antibiotics were performed using the pharmacophore modelling method and molecular docking. And piperine, withaferin, has some of the same amino acids Ala101, Val103, Glu166, Trp165, and Leu102. Based on the prediction of the promising potential test ligand compound is Corosolic acid. In addition to assessing drug-likeness, pharmacokinetic and toxicity parameters, corosolic acid also has the lowest binding energy among other compounds. Through a textual bioinformatics approach, molecular docking simulations can be used as a first step in the search for new drug candidates in silico by considering various aspects, starting from the physicochemical properties of protein-ligand compounds and the environment. Analysis during the docking process to ADMETOX is an analysis to see the effectiveness and in silico compound safety.